2018
DOI: 10.5194/acp-2018-443
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chlorine-initiated oxidation of n-alkanes under high NOx conditions: Insights into secondary organic aerosol composition and volatility using a FIGAERO-CIMS

Abstract: Abstract. Chlorine-initiated oxidation of n-alkanes (C8-12) under high nitrogen oxides conditions was investigated. Observed secondary organic aerosol yields (0.16 to 1.65) are higher than those for OH-initiated oxidation of C8-12 alkanes (0.04 to 0.35).A High-Resolution Time-of-Flight Chemical Ionization Mass Spectrometer coupled to a Filter Inlet for Gases and AEROsols (FIGAERO-CIMS) was used to characterize the gas-and particle-phase molecular composition. Chlorinated organics were 10 observed, which likely… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…In addition to the OH‐initiated oxidation pathway, S/IVOCs can also be oxidized by NO 3 radicals and O 3 , leading to the formation of SOA (Keyte et al., 2013; Riva et al., 2014, 2015, 2016; Wang & Hildebrandt Ruiz, 2018). However, the mechanism in the WRF‐Chem model only considers the oxidation of S/IVOCs by OH radical.…”
Section: Model Description and Improvementmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the OH‐initiated oxidation pathway, S/IVOCs can also be oxidized by NO 3 radicals and O 3 , leading to the formation of SOA (Keyte et al., 2013; Riva et al., 2014, 2015, 2016; Wang & Hildebrandt Ruiz, 2018). However, the mechanism in the WRF‐Chem model only considers the oxidation of S/IVOCs by OH radical.…”
Section: Model Description and Improvementmentioning
confidence: 99%
“…Additionally, only the oxidation reactions between S/IVOCs and OH are considered in most models, as this pathway is considered to be the most important (Hodzic et al., 2010; Pye & Seinfeld, 2010; Robinson et al., 2007; Shrivastava et al., 2011). However, recent experimental studies have revealed that the contributions of NO 3 ‐initiated and O 3 ‐initiated oxidations of S/IVOCs to SOA formation should also be considered (Keyte et al., 2013; Riva et al., 2014, 2015, 2016; Wang & Hildebrandt Ruiz, 2018). For example, the SOA yield from the ozonolysis of acenaphthylene was as high as 37% (Riva et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Nitryl chloride (ClNO2), a photolytic source of chlorine radicals (Cl·) and NO2, is produced from N2O5 where chloride-containing particles are present (Osthoff et al, 2008). Atomic chlorine is highly reactive and initiates VOC oxidation cycles and SOA formation (Wang and Hildebrandt Ruiz, 2018). The fate of the reactive uptake of N2O5 and subsequent impacts on oxidant and PM concentrations depend on individual particle surface composition (Gaston and Thornton 2016;McNamara et al 2020), which remains poorly constrained.…”
Section: Winter Atmospheric Chemical Cyclesmentioning
confidence: 99%
“…CC BY 4.0 License. Wang and Hildebrandt Ruiz, 2018;Bannan et al, 2019;Hammes et al, 2019;Lee et al, 2020;100 Thornton et al, 2020). Other online instruments such as particle into liquid sampler (PILS) coupled with ion chromatography (Bateman et al, 2010) and chemical analysis of aerosol online (CHARON) particle inlet coupled to proton-transfer-reaction time-of-flight mass spectrometry (PTR-TOFMS) instruments (Gkatzelis et al, 2018) can also be employed for collection and near real-time analysis of chemical compounds in aerosols.…”
Section: Introductionmentioning
confidence: 99%